Breastfeeding duration and associated factors between 1960 and 2000 - Danielle Soares de Oliveira; Cristiano S. Boccolini; Eduardo Faerstein; Eliseu Verly-Jr (Elsevier, 2017)
Objective: To describe a historical series on the median duration of breastfeeding in a population of mothers whose children were born from the 1960s onwards, identifying factors associated with the interruption of breastfeeding in each decade. Methods: Data were analyzed from the Pró-Saúde Study, a longitudinal epidemiological investigation started in 1999 among technical and administrative employees of a university in the state of Rio de Janeiro. Breastfeeding duration was collected in two study phases: Phase 1 (1999), and phase 4 (2011-2012). Of these, those who had at least one child and reported the duration of breastfeeding for the first child were selected (n = 1539). To analyze the duration of breastfeeding, survival curves were constructed using the Kaplan-Meier method and the effect of covariates on the duration of breastfeeding was estimated by Cox regression model. Results: It was found that the median duration of breastfeeding was higher in the 1990s and 2000s and lower in the 1970s, compared to the 1960s. In addition, there was an association between higher income and maternal age with breastfeeding interruption, which was focused in the 1970s. Conclusion: There was shorter duration of breastfeeding in the 1970s compared to the 1960s. Increased duration and prevalence of breastfeeding from the 1970s onwards coincided with the national trend and the promotion of this practice since 1980. Resumo: Objetivo: Descrever uma série histórica sobre a duração mediana da amamentação em população de mães com crianças nascidas a partir da década de 1960, identificando fatores associados à sua interrupção em cada década. Métodos: Foram analisados dados de 1539 participantes do Estudo Pró-Saúde (EPS), uma investigação epidemiológica longitudinal iniciada em 1999 entre trabalhadores técnico-administrativos de uma universidade localizada no Estado do Rio de Janeiro. Foram utilizadas informações sobre duração do aleitamento materno do primeiro filho coletadas em duas fases do EPS (1999 e 2011-12). Para análise da duração do aleitamento materno foram construídas curvas de sobrevida pelo método de Kaplan-Meier, e sua associação com covariáveis foi estimada pelo modelo de regressão de Cox. Resultados: Verificou-se que a duração mediana do aleitamento materno foi maior nas décadas de 1990 e 2000, e menor na década de 1970, em comparação com a década de 1960. Além disso, houve associação entre maior renda e faixa etária maternas com interrupção do aleitamento materno, que se concentrou na década de 1970. Conclusão: Observou-se menor duração do aleitamento materno na década de 1970 em relação à década de 1960. O aumento da duração e das prevalências de amamentação a partir da década de 1970 coincidiu com a tendência nacional e com a promoção dessa prática a partir de 1980. Keywords: Breastfeeding, Survival analysis, Child health, Time series, Palavras-chave: Aleitamento materno, Análise de sobrevida, Saúde da criança, Séries temporais